2020
DOI: 10.1021/acsanm.0c02295
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Surface Chemistry and Nanostructure of Carbon Nanotubes Facilitates the Detection of Aromatic Hydrocarbon Gases

Abstract: The benzene, toluene, and xylene (BTX) compounds currently utilized in many building materials and paints have been linked to deleterious health effects, and thus, monitoring the presence of these compounds is of increasing importance with respect to public health. As such, there is a critical need for next-generation low-cost, selective, and sensitive indoor BTX sensors. Current BTX detection systems require multicomponent, complex devices or require high power input to achieve BTX detection at meaningful con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In this study, benzene, toluene and xylene aromatic hydrocarbon gases had been detected using surface modifies SWCNTs. [182]…”
Section: Recognition Of Gas Moleculesmentioning
confidence: 99%
“…In this study, benzene, toluene and xylene aromatic hydrocarbon gases had been detected using surface modifies SWCNTs. [182]…”
Section: Recognition Of Gas Moleculesmentioning
confidence: 99%
“…At these concentrations, CO 2 can have substantial effects on human cognitive performance with statistically significant and meaningful reductions in decision-making performance. However, even at significantly lower concentrations, CO 2 is a useful IAQ metric because it serves as a proxy measure for human occupancy and the proportional impacts on IAQ. , Thus, there is an increasing interest in developing low-cost IAQ sensors for smart and connected buildings to monitor the concentration of CO 2 while being seamlessly integrated with existing ventilation systems. Among the potential gas-sensing technologies available, microelectromechanical systems (MEMS) gas sensors (i.e., electrochemical, acoustic, and optical sensors) are a promising avenue for low-cost and small-scale gas-sensing applications. In particular, adsorption-based electrochemical and electromechanical gas sensors have demonstrated potential for carbon dioxide (CO 2 ) monitoring in buildings, which is a market that has historically been dominated by optical nondispersive infrared (NDIR) sensors. In principle, in electrochemical and electromechanical gas sensor devices, the adsorption of a target gas analyte onto a chemically selective recognition layer induces a physical property change in the material, which is then transduced into a signal by the gas sensor. This physical property change can be a change in conductivity (i.e., electrochemical devices) or a change in mechanical behavior (i.e., resonance frequency).…”
Section: Introductionmentioning
confidence: 99%
“…3 These applications all rely on the specic surface properties of the CNTs promoting physisorption processes. Several studies have also shown that CNTs are excellent sorbents for organic species, and have been used in solid phase extraction, chromatographic analysis, and sensor development, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] although to the best of our knowledge there are few reports that examine adsorption of volatile organic compounds (VOCs) at their trace atmospheric level (ppb (v/v)). [24][25][26] This leads to concerns whether gaseous VOCs that are naturally present in the atmosphere could spontaneously be introduced into the CNTs during their storage and transportation, thereby affecting their desirable surface features as well as inuencing their toxicological properties.…”
Section: Introductionmentioning
confidence: 99%